ANTIOXIDANT ACTIVITY OF PHENOLIC EXTRACTS FROM BLACK TEA - Albaldawi, Amira M; Chechan, Rukaibaa A (Al-Nahrain Journal of Science, 2010)
Phenolic compounds extracts from black tea (obtained from local markets) were extracted byhot and cold methods to test their antioxidant activity by determination of thiobarbituric acid No.(TBA%). Effect of different concentrations( 0.02, 0.04, 0.08 ) % of extracts and time of incubation(30days) at 40 C were studied, hot method phenolic extract(S2)gave a positive concentration effecton antioxidant activity, cold method phenolic extract ( S1 ) gave a limited concentration effect.S1 and S2 gave continuous decrease in TBA % after different periods of incubation time, S2showed higher antioxidant activity than S1,S1 and S2 antioxidant activity were compared withsynthetic antioxidants BHA and BHT and natural antioxidant activity -Tocopherol.S1 and S2 gavehigher activity than BHA and BHT on the other hand -Tocopherol showed inhibition inantioxidant activity.